Organização da demanda de um Centro de Especialidades Odontológicas - Saliba, Nemre Adas [UNESP]; Nayme, João Guilherme Rodrigues [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Cecilio, Lenise Patrocinio Pires [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (FapUNIFESP (SciELO), 2013)
Introduction: Secondary care in oral health in Brazil is still a little researched topic. Objective: The aim of this study was to analyze the resolution of dental services in SUS based on the referral to secondary attention and backreferral to primary attention. Methodology: It’s a descriptive, quantitative study that used secondary data collected from dental records of patients seen at Centre of Dental Specialties (Ceo) in a city of São Paulo State. Result: It was analyzed 1030 dental records. Just 1236 proceedings received referral to Ceo and among then, 86.4% showed the first attendance on Basic Health Unity (UBS) through spontaneous demand and 50.4% (n=623) received referral to endodontic treatment. There was evasion of 2.27% of studied population (n=28) on the first specialized consultation. Among 1208 proceedings that started the treatment in Ceo, 62.6% (n=757) were finalized and received back-referral to primary attention, that finalized 61.1% (n=463) of proceedings. To conclude the treatment, considering the time spent in Ceo and primary attention, there was variation according to specialty: periodontics – 62 days (sd ±68) and endodontics – 71 days (sd ±51.8), requiring 3 consultations in average, regardless specialty. Conclusion: The Centre of Dental Specialties gave referral and attention to the majority of demand, regardless specialty. However, there are many cases of evasion during dental treatment, alerting managers to develop methods to entice these patients, reducing service expenses and raising solvability of dental procedures previously initiated.

Introdução: A Atenção Secundária em saúde bucal no Brasil ainda é um assunto pouco pesquisado. Objetivo: Analisar a resolubilidade dos serviços odontológicos do Sistema Único de Saúde, com base na referência para a atenção secundária e a contrarreferência à atenção primária. Metodologia: Trata-se de um estudo descritivo, quantitativo, que utilizou dados secundários coletados dos prontuários dos pacientes atendidos no Centro de Especialidades Odontológicas de um município do Estado de São Paulo. Resultado: Do total de 1030 prontuários analisados, verificaram-se 1236 procedimentos referenciados para atenção especializada. Destes, 86,4% deram entrada na Unidade Básica de Saúde por livre demanda e 50,4% (n=623), para especialidade de Endodontia. Houve evasão de 2,2% (n=28) já na primeira consulta especializada. Nos pacientes que deram início ao tratamento especializado, foram realizados 1.208 procedimentos no Centro de Especialidades Odontológicas, tendo sido 62,6% (n=757) concluídos e contrarreferenciados para a Atenção Primária, que finalizou 61,1% (n=463) dos procedimentos. Para a conclusão do tratamento, considerando o tempo no Centro de Especialidades Odontológicas e na Atenção Básica, houve variação de acordo com a especialidade: Periodontia, 62 dias (dp= ±68), e Endodontia, 71 dias (dp= ±51,8), sendo necessárias três consultas em média, independentemente da especialidade. Conclusão: O Centro de Especialidades Odontológicas referencia, contrarreferencia e atende à maioria da demanda, independentemente da especialidade. Porém, ainda há muita evasão durante o tratamento odontológico, servindo de alerta para os gestores desenvolverem métodos de controle dos pacientes atendidos, com vistas à diminuição de gastos e ao aumento da resolutividade dos serviços, com a conclusão dos tratamentos iniciados.
Organization of the demand for a Centre of Dental Specialties
Keywords: Specialties dental; Unified Health System; Public health; Especialidades odontológicas; Sistema Único de Saúde; Saúde pública